2010
DOI: 10.1038/gt.2010.155
|View full text |Cite
|
Sign up to set email alerts
|

Systemic human Netrin-1 gene delivery by adeno-associated virus type 8 alters leukocyte accumulation and atherogenesis in vivo

Abstract: Atherosclerosis is an inflammatory disorder of arteries. Atherosclerotic plaque, in its early to intermediate stages, is composed largely of lipid-engorged foam cells. These foam cells are derived from the trafficking of monocytes (Mo) into the arterial intima, attracted to the site by chemoattractants. Given that foam cells are derived from the trafficking of Mo, the use of Netrin-1, an Mo chemorepellent, may be useful in limiting Mo accumulation and subsequent plaque formation. To investigate the potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…8 In another study, intravenous delivery of NTN1 to hypercholesterolemic mice using viral vectors increased NTN1 expression, presumably on endothelial cells, and resulted in prevention of MΦ infiltration of the nascent plaque. 13 Recent studies have shown that coronary endothelial cells express NTN1, which inhibits migration of human monocytes in vitro.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%
“…8 In another study, intravenous delivery of NTN1 to hypercholesterolemic mice using viral vectors increased NTN1 expression, presumably on endothelial cells, and resulted in prevention of MΦ infiltration of the nascent plaque. 13 Recent studies have shown that coronary endothelial cells express NTN1, which inhibits migration of human monocytes in vitro.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%
“…Today, impressive results have been reported in neonatal, adult and even aged animals. Some of these examples include AAV-1 mediated gene therapy for Pompe disease, limb-girdle muscular dystrophy (LGMD) and myotonic dystrophy [33-35], AAV-6 mediated gene therapy for DMD and facioscapulohumeral muscular dystrophy [25,36-38], AAV-8-mediated gene therapy for DMD, LGMD and atherosclerosis [26,39-41], and AAV-9 mediated gene therapy for cardiomyopathy, lysosomal storage disorders and neuronal diseases [42-51]. …”
Section: Systemic Gene Delivery With Aav In Rodentsmentioning
confidence: 99%
“…As a result, ongoing inflammation within adipose tissue resulted in decreased glucose tolerance in a glucose tolerance test, with the development of insulin resistance [16]. Importantly, using an adenovirus vector to deliver hNetrin-1 in vivo resulted in a significant reduction in plaque formation, as determined by larger aortic lumen size, thinner intima-media thickness, and reduced blood velocity, thus demonstrating that netrin-1 is a viable target in atherosclerosis [81].…”
Section: Neuronal Guidance Proteins In Atherosclerosismentioning
confidence: 96%